Renaissance: The Rise Of Art, Culture and Science in Europe - Hajar Mahyana; Umar Affandi; Anis; Indah Setiawan; Nurasiah (Universitas Syiah Kuala and Collaboration Yayasan Yusda Edu Indonesia, 2025)
This article examines the Renaissance as a period of revival of art, culture, and science in Europe from the 14th century to the modern era, which emerged after the collapse of the Western Roman Empire in 476 AD and the dominance of the church during the Dark Ages. The Renaissance, derived from the Latin